The Risks of Early Complications from Level II Axillary Clearance in Modified Radical Mastectomy: Level II Axillary Clearance in Modified Radical Mastectomy - Jamil, Tariq; Tarar, Javed Mirdad; Nasir, Ferwa; Zahid, Muhammad Maqsood; Ali, Akhtar (Pakistan Journal of Health Sciences, 2024)
The second leading cause of cancer fatalities in women is breast cancer. Complete breast tissue removal and axillary lymph node removal are performed in a modified radical mastectomy. Seroma is the most frequent surgical complication. Due to inadequate data, our study would give significant data on this issue and wound infection. Objective: To determine the most prevalent early difficulties observed by early breast cancer patients after a modified radical mastectomy with axillary clearing. Methods: This descriptive research included 135 women who had a modified radical mastectomy with level II axillary clearance for early-stage breast cancer. After surgery, we monitored these patients in the Breast Clinic for up to a month for any issues. This data set used SPSS version 24.0. Results: The patients' average age was 50.12 ± 7.44 years. Seroma development was the most prevalent consequence found in 47 (34.8%) patients, while 35 patients (24.9%) experienced edema of the arm. In 15 patients (11.1%) wound infection was noted, 12 patients (8.9%) had paresthesia, 8 patients (5.9%) had a hemorrhage, in 7 patients (5.2%) hematoma was noted, and 7 patients (5.2%) developed skin flap necrosis. In 5 patients (3.7%), paralysis of the serratus anterior and Latissimus Dorsi muscles was detected. Conclusions: A modified radical mastectomy can cause complications like seroma formation, wound infection, arm edema, hemorrhage, skin flap necrosis, serratus anterior muscle paralysis, intercostobrachial nerve paresthesia, and axillary dissection. Correct postoperative care can detect these issues.